PENGAMALAN NILAI-NILAI PANCASILA DALAM KEHIDUPAN SANTRI DI PONDOK PESANTREN ASSALAFI AL-FITHRAH SURABAYA - Akbar Rayhudu Prince Twindhar; Muhammad Turhan Yani (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
Pancasila, as the foundation of the Indonesian state, plays an important role in shaping the character and values of the lives of santri. Santri, who are students at Islamic boarding schools, are expected not only to master religious knowledge but also to apply the principles of Pancasila in their daily lives. This research discusses the practice of Pancasila values in the lives of students at Pondok Pesantren Assalafi Al-Fithrah Surabaya. The purpose of the research is to understand how the values of Pancasila are practiced in the learning process and daily life of the students. This research uses a qualitative approach with a descriptive research type. Data collection methods through observation, interviews, and documentation. Data analysis techniques through data collection, data reduction, data presentation, and drawing conclusions. The research results show that the values in Pancasila are not only taught as a subject but also applied in the ethics and behavior in the lives of the students. The values of divinity, humanity, and unity serve as the foundation for social interactions at the boarding school. This research concludes that Islamic boarding schools also play a very important role in instilling the values of Pancasila, so that students can become individuals with noble character and contribute positively to society.